ASPECTS OF THE DEVELOPMENT OF INNOVATIVE FINANCIAL TECHNOLOGIES IN UKRAINE - BOHACH, Yurii; BOHACH, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines aspects of the development of innovative financial technologies. It is shown that in the era of digital transformation of the economy and society, the increasing and increasingly active use of electronic communications and the penetration of information and communication technologies into all spheres of social life, in particular the economic, The task of creating and actively applying progressive innovative financial technologies is becoming more urgent. Both the effective functioning and development of the country's financial and directly banking system, as well as the efficiency of business entities, and hence the sectors and industries of the regional and national economic systems, depend on this. Therefore, the purpose of the article is to identify and substantiate aspects of the development of innovative financial technologies in Ukraine. A number of recommendations have been developed for the creation, development and more active use of innovative financial technologies in Ukraine. It is shown that innovations in the financial sector allow the country's financial system and directly economic agents to maintain competitive advantages, enter new markets and gain leadership in global financial markets. Technological improvements, improvements in financial business processes and directly financial technologies and services help to effectively combat international competition in this area. Moreover, the implementation of innovative financial technologies must take into account the specifics and needs of each specific segment of the financial services market, which means the development and modification of products, services and business processes in accordance with the requirements and preferences, requests of financial services consumers.
Keywords: financial instruments; innovative technologies; digitalization; financial systems; artificial intelligence; blockchain; financial inclusion; FinTech; digital assets; Big Data; financial technology regulation; digital payments